ANALISIS PENGARUH KINERJA PEGAWAI TERHADAP KUALITAS PELAYANAN DI UPT RUMAH SAKIT KHUSUS MATA PROVINSI SUMATERA UTARA - Jasa Maruasas Sirait; Albiner Siagian; Selamat Ginting (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2022)
Every organization, both government and private, is required to be able to optimize its human resources, as well as how to manage human Resources. Human resource management cannot be separated from the factor of employees who are expected to be able to achieve as much as possible to achieve the goals of a government organization. The purpose of this research is to determine the effect of employee performance on the quality of service at the UPT Special Eye Hospital, North Sumatra Province. The design of this study was to use a case control with chi-square test. The sample in the study amounted to 32 respondents. The results showed that there were 16 respondents in the case group and 16 respondents in the control group. There is a significant relationship between employee quality variables (p-value = 0.026, OR = 0.111 (0.019-0.659)), employee communication (p-value = 0.037, OR = 0.086 (0.009-0.815)) and employee abilities (p-value = 0.034, OR=6,600(1,403-31,051)) on service quality and it is known that the employee performance variable that most dominantly affects service quality is the employee's ability variable where (p-value=0,034, OR=6,600). Although the influence of employee performance on service quality at UPT Hospital Especially for the eyes of North Sumatra, it is included in the